Cost of Elective Labor Induction Compared With Expectant Management in Nulliparous Women. Issue 1 (July 2020) - Einerson, Brett D.; Nelson, Richard E.; Sandoval, Grecio; Esplin, M. Sean; Branch, D. Ware; Metz, Torri D.; Silver, Robert M.; Grobman, William A.; Reddy, Uma M.; Varner, Michael
Abstract : OBJECTIVE: To compare the actual health-system cost of elective labor induction at 39 weeks of gestation with expectant management. METHODS: This was an economic analysis of patients enrolled in the five Utah hospitals participating in a multicenter randomized trial of elective labor induction at 39 weeks of gestation compared with expectant management in low-risk nulliparous women. The entire trial enrolled more than 6, 000 patients. For this subset, 1, 201 had cost data available. The primary outcome was relative direct health care costs of maternal and neonatal care from a health system perspective. Secondary outcomes included the costs of each phase of maternal and neonatal care. Direct health system costs of maternal and neonatal care were measured using advanced costing analytics from the time of randomization at 38 weeks of gestation until exit from the study up to 8 weeks postpartum. Costs in each randomization arm were compared using generalized linear models and reported as the relative cost of induction compared with expectant management. With a fixed sample size, we had adequate power to detect a 7.3% or greater difference in overall costs. RESULTS: The total cost of elective induction was no different than expectant management (mean difference +4.7%; 95% CI −2.1% to +12.0%; P =.18). Maternal outpatient antenatal care costs were 47.0% lower in the induction arm (95% CI −58.3% to −32.6%; P <.001). Maternal inpatient intrapartum and delivery care costs, conversely, were 16.9% higher among women undergoing labor induction (95% CI +5.5% to +29.5%; P =.003). Maternal inpatient postpartum care, maternal outpatient care after discharge, neonatal hospital care, and neonatal care after discharge did not differ between arms. CONCLUSION: Total costs of elective labor induction and expectant management did not differ significantly. These results challenge the assumption that elective induction of labor leads to significant cost escalation. Abstract : Total actual costs of elective labor induction do not differ significantly from expectant management among term nulliparous women enrolled in a randomized controlled trial.